Structural basis for the inhibition of IAPP fibril formation by the co-chaperonin prefoldin - Ricarda Törner; Tatsiana Kupreichyk; Lothar Gremer; Elisa Colas Debled; Daphna Fenel; Sarah Schemmert; Pierre Gans; Dieter Willbold; Guy Schoehn; Wolfgang Hoyer; Jerome Boisbouvier (Nature Communications, 2022)
Integrated kinetic and structural investigations reveal that the ubiquitous co-chaperonin prefoldin interacts with its coiled-coil helices on the islet amyloid polypeptide fibril surface and fibril ends to inhibit fibril elongation and secondary nucleation.